Exploring the Use of White Lies in Patient Care Process by Triangulation Method - alireza nikbakht nasrabadi; soodabeh joolaee; elham navvab; maryam esmaeili; mahboube shali (Kerman University of Medical Sciences, 2021)
Introduction: Being in a situation to use white lie is a challenging experience for healthcare providers. Recognizing the situations that facilitate white lies and providing solutions to them are effective in providing patients with the truth about their treatment and reducing white lies. The objective of this study was to explore the experiences of patients' families, nurses, and physicians in using white lies during care process.   Methods: This study, with a triangulation approach, was conducted in 2018 at the hospitals affiliated to Tehran University of Medical Sciences. Data were collected in two qualitative and quantitative phases from three sources including patients' families, nurses, and physicians. In the quantitative phase, 300 samples were selected by random sampling to complete a researcher-made questionnaire. Descriptive statistics and frequency tables were used to analyze the quantitative data. In the qualitative phase, 30 individuals from above-mentioned sources were selected by purposive sampling to participate in the face-to-face and semi-structured interviews. Data analysis in qualitative phase was done by Graneheim and Lundman's conventional content analysis. In the final step, quantitative and qualitative data were compared and interpreted. Results: The findings of qualitative phase were summarized in four categories (inappropriate situation, patient expediency, surrounding frameworks, and communication bridges) and eight subcategories. In the quantitative phase, the highest score was related to the category of patient expediency. It was also found that the findings of qualitative and quantitative phases were consistent and complementary to each other. Conclusion: According to the findings, the use of white lies was for patient's benefit and to create an appropriate situation for telling the truth. In this regard, providing appropriate guidelines in accordance with the culture, therapeutic goal, and understanding of patients can enhance caregivers' skills in rendering information to patient. The findings of this study can be used as a guide in other qualitative and quantitative researches regarding the use of white lie in patient care and its consequences.